On the top of ARB N/L type Ca channel blocker leads to less elevation of aldosterone. Issue 5 (16th September 2016) - Konoshita, Tadashi; Kaeriyama, Saori; Urabe, Machi; Nakaya, Takahiro; Yamada, Mika; Ichikawa, Mai; Yamamoto, Katsushi; Sato, Satsuki; Imagawa, Michiko; Fujii, Miki; Makino, Yasukazu; Zenimaru, Yasuo; et al.
Abstract : The activation of the renin–angiotensin system (RAS) is one of the unfavourable characteristics of calcium channel blocker (CCB). N type calcium channel is thought to be involved in renin gene transcription and adrenal aldosterone release. Accordingly, N/L type CCB has a possibility of less elevation of plasma aldosterone concentrations (PAC) among CCBs. In a monotherapy study, we had already demonstrated that N/L type CCB leads to less activation of the RAS compared with L type CCB. The objective of this study is to substantiate the hypothesis that at the condition of additive administration on the top of an angiotensin receptor blocker (ARB), still N/L type CCB leads to less elevation of PAC compared with L type one. Subjects were 60 hypertensives administered with valsartan. As an open label study, amlodipine (L type) or cilnidipine (N/L type) were administered on the top of valsartan (ARB) in a cross-over manner. Results were as follows (valsartan+amlodipine compared with valsartan+cilnidipine): systolic blood pressure (SBP)/diastolic blood pressure (DBP) (mmHg): 132±10/76±10 compared with 131±10/77±9, P =0.95/0.48, plasma renin activity (PRA) (ng/ml·h): 2.41±2.67 compared with 2.00±1.50 P =0.20, PAC (pg/ml): 77.3±31.0 compared with 67.4±24.8, P <0.05, urinary albumin excretion (UAE) (mg/gCr): 105.9±216.1 compared with 73.9±122.2, P <0.05. Thus, PAC at cilnidipine was significantly lower than those at amlodipine in spite of the comparable BP reductions. Besides, UAE was significantly lower at cilnidipine. In conclusion, on the top of the ARB, it is suggested that cilnidipine administration might lead to less elevation of PAC and reduction in UAE compared with amlodipine.